Industrial digital transformation : accelerate digital transformation with business optimization, AI, and Industry 4.0 - Nath, Shyam Varan; Dunkin, Ann; Chowdhary, Mahesh; Patel, Nital (Packt Publishing, 2023)
Delve into industrial digital transformation and learn how to implement modern business strategies powered by digital technologies as well as organization and cultural optimization About This Audiobook Identify potential industry disruptors from various business domains and emerging technologies Leverage existing resources to identify new avenues for generating digital revenue Boost digital transformation with cloud computing, big data, artificial intelligence (AI), and the Internet of Things (IoT) In Detail Digital transformation requires the ability to identify opportunities across industries and apply the right technologies and tools to achieve results. This audiobook is divided into two parts with the first covering what digital transformation is and why it is important. The second part focuses on how digital transformation works. After an introduction to digital transformation, you will explore the transformation journey in logical steps and understand how to build business cases and create productivity benefit statements. Next, you'll delve into advanced topics relating to overcoming various challenges. Later, the audiobook will take you through case studies in both private and public sector organizations. You'll explore private sector organizations such as industrial and hi-tech manufacturing in detail and get to grips with public sector organizations by learning how transformation can be achieved on a global scale and how the resident experience can be improved. In addition to this, you will understand the role of artificial intelligence, machine learning and deep learning in digital transformation. Finally, you'll discover how to create a playbook that can ensure success in digital transformation. By the end of this audiobook, you'll be well-versed with industrial digital transformation and be able to apply your skills in the real world. Audience This audiobook is for IT leaders, digital strategy leaders, line-of-business leaders, solution architects, and IT business partners looking for digital transformation opportunities within their organizations. Professionals from service and management consulting firms will also find this audiobook useful. Basic knowledge of enterprise IT and some intermediate knowledge of identifying digital revenue streams or internal transformation opportunities are required to get started with this audiobook.